ANALISIS MANAJEMEN RISIKO DENGAN METODE HIRADC PADA INDUSTRI MEUBEL UD. ULUM JAYA - Muhammad Ilham Rizqi Dermawan; Moch Sahri (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
The International Labor Organization (ILO) explained that 2.78 million workers die every year due to work accidents and occupational diseases. Around 2.4 million (86.3%) of these deaths were due to occupational diseases, while more than 380,000 (13.7%) were due to work accidents. Community groups working in the informal sector have not yet received attention in the field of Safety and Health. the Occupational Health. The furniture industry is one of the informal industries that has a high level of complexity. This industry is an informal industry using wood as the basic material, where the process produces a lot of wood fibers or very small dust in the work environment. In a total time of approximately 10 working hours, workers are exposed to dust and other work hazards, this causes work accidents and occupational diseases, to reduce or eliminate hazards that can cause accidents in the workplace, a risk management is needed. requirements of OHSAS 18001 clause 4.3.1 that the organization must establish procedures and carry out hazard identification, risk assessment and determining control. The results of the study show that the work process that has the highest risk is in the formation process work unitKeywords: Occupational Safety and Health, Meubel Industry, HIRADC